Good, Bad and Very Bad Part-time Jobs for Women? Re-examining the Importance of Occupational Class for Job Quality since the 'Great Recession' in Britain. (August 2018) - Warren, Tracey; Lyonette, Clare
Britain has long stood out in Europe for its extensive but poor-quality part-time labour market dominated by women workers, who are concentrated in lower-level jobs demanding few skills and low levels of education, offering weak wage rates and restricted advancement opportunities. This article explores trends in part-time job quality for women up to and beyond the recession of 2008/9, and asks whether post-recessionary job quality remains differentiated by occupational class. A pre-recessionary narrowing of the part-time/full-time gap in job quality appears to have been maintained for the women in higher-level part-time jobs, while part- and full-timers in lower-level jobs suffered the worst effects of the recession, signalling deepening occupational class inequalities among working women.